Review of the Authority of the House of Representatives in Removing Constitutional Court Judges - Carissa Patricia Hong; Luverne Pujian Quinn; Jelita Safitri Ananda; Omega Kharisma; Tundjung Herning Sitabuana (QISTINA: Jurnal Multidisiplin Indonesia, 2023)
The Constitutional Court of the Republic of Indonesia is a high state institution in the Indonesian constitutional system which is the holder of judicial authority together with the Supreme Court. In the dismissal of the Constitutional Court Judges it is very urgent to decide because it relates to the independence of the Constitutional Court Judges. The longer the case, the political pressure from the DPR as a fellow state high institution will result in the instability of the legal system in Indonesia. Moreover, at this time the DPR has confirmed that it will not annul the replacement of Constitutional Justice Aswanto, so it is important that the DPR's actions be immediately tried by the judicial authority, in casu the Constitutional Court. The formulation of the problem in this study is what is the authority of the DPR in removing Constitutional Court judges? This study uses normative research with descriptive research specifications. The province's request for an examination is very priority and also so that the Court suspends all actions aimed at replacing a serving Constitutional Justice in a manner or procedure outside of the provisions in Article 23 of the Constitutional Court Law, and it is also not justified to issue a stipulation that legalizes the action as the applicant requested in the petitum provision. The petition of the applicant is based on strong reasons which are non-nobis solum sed omnibus (not for us alone, but for everyone), because the independence of the MK as guardian of constitutional rights is at stake.